Preparing Police Leaders of the Future: An Educational Needs Assessment - Huey, Laura (2019)
Given that there is very little research available – in Canada or elsewhere – on police leadership education and training, and police are being challenged to work in increasingly complex decision and task environments, an empirical analysis in this area is both timely and of significance utility for shaping both public policy and police practice. This study answers the following research questions: RQ1. What forms of police leader education and training currently exist for Canadian police leaders? RQ2. Are these courses and/or programs suitable for the needs of police leaders given the demands they face? To answer these questions, we conducted a two-part study. The first part consisted of an environmental scan of training and educational programs for police leaders. This scan helped us by providing a basis for understanding what current program offerings exist for Canadian police leaders – both within Canada and across the globe. The goal of the second part of the study was to develop a needs assessment. Our assessment and recommendations are based on interviews with 29 senior officers (Inspector to Chief ranks) from police organizations across Canada. Using an interview guide, we asked for their views on police leadership training and education, what forms of education should be available, and what types of education (ie. content, modes of delivery) would be most useful for meeting the needs of their respective positions